Study of thermoreversible hydrogel made from a triblock copolymer and graphene oxide - Hafizah Awang (2013)
Aqueous solutions of a mixture consisting of a PEO-PPO-PEO triblock copolymer, Pluronic F127 (EO100-PO65-EO100) and Graphene Oxide were prepared and studied. Thermoreversible micellization and gelation properties of the mixture were investigated as a function of temperature, mixture composition and polymer concentration of GO to F127 by means of micro DSC and rheology. The completely thermoreversible behaviors of micellization and gelation were observed for the solutions of F127 with a concentration of 15 wt% and various GO/F127 molar ratios. At a given concentration of F127, three effects of GO on F127 were found as follows. (a) For rheology test, the presence of GO causes the sol-gel transition ceased to exist, so that there is no such point to define the sol-gel transition even though G’ has shown a steep increase in the region. (b) For micro DSC test, the mixture thermal properties results show that adding a controlled amount of GO will cause the mixture to increase the critical micelization temperature (CMT) and micelization offset temperature (Toff) in heating process. (c) For cooling process, presence of GO will increase its critical demicelization temperature (CDMT) and demicelization offset temperature. (d) Increasing the concentration of GO in the mixture will increase the temperature for peak Cp to occur.